The global context for new directions for child and adolescent development - Grigorenko, Elena L. (New directions for child and adolescent development ;, 2015)
This is the 147th volume in this Jossey-Bass series New Directions for Child and Adolescent Development. Its mission is to provide scientific and scholarly presentations on cutting edge issues and concepts in this subject area. Each volume focuses on a specific new direction or research topic and is edited by experts from that field.